Mechanisms of Interaction Between Law Enforcement Agencies and Private Security Companies in Crime Prevention - Ilovača, Kristijan (Emerging Frontiers Library for The American Journal of Political Science Law and Criminology, 2026)
The article is devoted to the study of the evolution of mechanisms of interaction between state law enforcement agencies and the private security sector in the context of the accelerated development of dual-use technologies. The relevance of the study is determined by the fact that the traditional state monopoly on security instruments is gradually losing its exclusive character due to the broad availability of commercial high-tech solutions (AI systems, unmanned platforms, cyber infrastructures). The research examines contemporary formats of public-private partnership, identifies the key barriers to their institutional and technological integration, and analyzes the possibilities of their gradual overcoming. Special emphasis is placed on the transition from minimal forms of cooperation, based mainly on isolated information exchange, to comprehensive, highly integrated smart security systems. The aim of the study is to construct a theoretical model of adaptive risk management arising from the use of private technological solutions in the field of public security. To achieve this aim, methods of systems analysis, comparative legal research, and case studies (based on successful practices of countering identity theft) are applied. The empirical and theoretical foundation of the research consists of foreign sources published in recent years. In the final part, the author’s concept of a hybrid security architecture is formulated. The obtained results are of interest to the heads of law enforcement agencies, corporate security practitioners, and specialists involved in the development and updating of regulatory legal acts.